2021
DOI: 10.1002/ppul.25786
|View full text |Cite
|
Sign up to set email alerts
|

Acute bronchiolitis in Switzerland – Current management and comparison over the last two decades

Abstract: Background Although international guidelines and Cochrane reviews emphasize that therapies do not alter the natural course of acute viral bronchiolitis (AVB), they are still prescribed frequently. This survey evaluated self‐reported management of AVB by Swiss pediatricians in 2019 and compared it with previous surveys. Methods We performed a cross‐sectional online survey of all board‐certified pediatricians in Switzerland in November 2019 and compared the reported use of therapies with that reported in the 200… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 39 publications
2
5
0
1
Order By: Relevance
“…Our results are, overall, in line with previous reports [ 8 11 ]. The strength of our study lies first, in that we were able to retrieve robust data from patients presenting with acute bronchiolitis between three distinct periods of observation.…”
Section: Discussionsupporting
confidence: 94%
“…Our results are, overall, in line with previous reports [ 8 11 ]. The strength of our study lies first, in that we were able to retrieve robust data from patients presenting with acute bronchiolitis between three distinct periods of observation.…”
Section: Discussionsupporting
confidence: 94%
“…All 27 trials had random sequence generation and provided adequate information on incomplete outcomes, selective reporting, and other bias. [21–47] Twenty studies reported sufficient information on allocation concealment, [3–32,36,38–45,47] and 18 RCTs elaborated the blinding of participants and personnel clearly. [21–23,25–28,30–32,36,39–45,47] All trials described blinding of outcome assessments, except for 10 studies, [24,28,29,33–35,37,38,40,46] which provided insufficient information.…”
Section: Resultsmentioning
confidence: 99%
“…Presently, management of AB mainly consists of supportive care, supplemental oxygen, adequate hydration, mechanical ventilatory support, antibiotics, corticosteroids, chest physiotherapy, magnesium sulfate, and nebulized hypertonic saline (NHS). [11–21] Previous studies have reported that NHS can benefit infants with AB. [21–47] It has been reported that NHS can induce osmotic flow of water into the lung mucosa, rehydrate airway surface lipid, increase mucosa cilia function, and enhance airway obstruction by clearing sputum outside of the bronchi.…”
Section: Introductionmentioning
confidence: 99%
“…Sin embargo, no existe ninguna herramienta similar al cuestionario aquí presentado que permita evaluar si los conocimientos de los padres son los correctos y si sus prácticas se corresponden con lo que recomienda la literatura para esta patología. Además, hay que destacar que entre los propios pediatras existen discrepancias entre las guías clínicas y el abordaje que se realiza en la bronquiolitis, lo cual también puede influir en la educación sanitaria que se da a los cuidadores 28 .…”
Section: Discussionunclassified